Promoting the linguistic and intercultural education of pre-primary learners and of their parents in the context of Italian as an L2 courses in Venice - Valeria Tonioli (University of Bologna, 2021)
In our paper we will present an experimental proposal of teaching Italian as a second language and promoting plurilingualism and the preservation of the mother tongue in a course organized for children of pre-school services and for their parents. The proposal was financed by a FAMI project, called VOCI, a leaded by the municipality of Venice in partnership with the University Ca' Foscari. All the project was carried out between 2019 and 2021. The project aimed at experimenting actions to facilitate the learning of Italian as a second language (L2) together with contents of civic education for vulnerable learners. Thanks to recent studies it has emerged the need to promote courses of a second language and at the same time to promote all children's language repertoires. During the experimental proposal that we will present, we organized such type of courses for minors of pre-school services and for their parents. We focused on vocabulary and syntactical aspects useful to tell stories. We will present the syllabus of the course, the activities and the results of two focus group.